2022
DOI: 10.20469/ijbas.8.10001-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leadership Styles in Organizational Citizenship Behavior

Abstract: Leaders are thought to be the most important part of any organization as they show the ways for individuals by directing organizational activities toward a mutual goal. As organizations face new obstacles in creating a profitable place within relentless markets filled to the brim with ambitious individuals, skilled leaders are one of the primary links necessary for surmounting the aforementioned challenges. The research is set to observe the relationship between leadership styles and organizational citizenship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Previous studies by Blaique (2022), Nikookar-Gohari et al (2021), and Widodo and Yusuf (2021) also found that visionary leadership affects OCB. Dedic et al (2022) also demonstrated that leadership style leads to OCB. These findings give rise to the first hypothesis (H) of this research: H1: Visionary leadership positively affects OCB…”
Section: Visionary Leadership and Organizational Citizenship Behaviormentioning
confidence: 91%
“…Previous studies by Blaique (2022), Nikookar-Gohari et al (2021), and Widodo and Yusuf (2021) also found that visionary leadership affects OCB. Dedic et al (2022) also demonstrated that leadership style leads to OCB. These findings give rise to the first hypothesis (H) of this research: H1: Visionary leadership positively affects OCB…”
Section: Visionary Leadership and Organizational Citizenship Behaviormentioning
confidence: 91%
“…According to Ullah et al (2021) that supports these correlations, employees are more likely to act in ways that advance the performance and general well-being of the company when their leaders model these attributes. By using successful leadership styles, the contributions essentially aim to clarify the relevant behavioral patterns that are essential for establishing Organizational Citizenship Behaviors (OCBE) (Dedic et al, 2022) . Specifically designed for the area, the focus lies on carefully addressing the weakest aspects to optimize the effect and coordinating leadership styles with company culture to achieve the best outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the current competitive landscape, organizations must prioritize their duties and procedures in order to enhance their performance and ensure their survival and growth. Given the current circumstances, the primary goals of every progressive organization are to enhance the capacities of individuals and eventually improve the performance of the institution [22]. The performance of workers is the result of their unique behaviors, which directly contribute to achieving the goals of the organization.…”
Section: Discussionmentioning
confidence: 99%